Usefulness of Eurasian Magpies (Pica pica) for West Nile virus Surveillance in Non-Endemic and Endemic Situations - Sebastian Napp; Tomás Montalvo; César Piñol-Baena; Maria Belén Gómez-Martín; Olga Nicolás-Francisco; Mercè Soler; Núria Busquets (Viruses, 2019)
In September 2017, passive surveillance allowed the detection of West Nile virus (WNV) lineage 2 for the first time in northern Spain in a northern goshawk (Accipiter gentilis). However, a cross sectional study carried out in Eurasian magpies (Pica pica) in a nearby area evidenced that WNV had been circulating two months earlier. Therefore, active surveillance in Eurasian magpies proved its effectiveness for the early detection of WNV in a non-endemic area. Further surveys in 2018 and the beginning of 2019 using young magpies (i.e., born after 2017) showed the repeated circulation of WNV in the same region in the following transmission season. Therefore, active surveillance in Eurasian magpies as well proved to be useful for the detection of WNV circulation in areas that may be considered as endemic. In this manuscript we present the results of those studies and discuss reasons that make the Eurasian magpies an ideal species for the surveillance of WNV, both in endemic and non-endemic areas.